Burbank-Van Voorhis families papers - Burbank, Sidney, 1807-1882.; Burbank, Sullivan, 1776-1862.; Van Voorhis, Daniel; Van Voorhis, Edith Burbank
Correspondence, diaries, and military papers of Burbank and Van Voorhis family members spanning the War of 1812, Mexican War, Civil War, and the American occupation of the Philippines in the early 20th century.
Diary of Sullivan Burbank pertaining primarily to his service during the War of 1812 at forts in New York State and Detroit, Mich., area; troop movements; passing American and British ships; and an Indian council held at General Winfield Scott's headquarters. Diaries of Sidney Burbank document negotiations with Indians in Florida; removal of the Winnebago Indians from the Illinois territory to the western side of the Mississippi River; Burbank's command of the Jefferson Barracks, St. Louis, Miss., during the Mexican War; his Civil War service including participation in the battles of Fredricksburg, Va., and Gettysburg, Pa., and command of Newport Barracks, Ky.; and journeys to Massachusetts, New Orleans, La., and Texas. Includes correspondence and a file of reports kept by Daniel Van Voorhis during his posting with the Philippine Scouts at Regan Barracks, Albay, Philippines, 1911-1913, documenting relations between American troops and the populace. Also includes typewritten transcripts of letters from Daniel's wife, Edith Burbank Van Voorhis, to her family written during their years in the Philippines. Collection also includes an August 1912 issue of the Filipino newspaper, El Heraldo Bico.
Members of the Burbank and Van Voorhis (Voorhees) families including Sullivan Burbank, U.S. Army captain; Sidney Burbank, U.S. Army brigadier general; and Daniel Van Voorhis, U.S. Army major.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Scott, Winfield, -- 1786-1866.; Burbank family; Voorhees family; United States. -- Army. -- Philippine Scouts; Heraldo bico; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Indians of North America -- Government relations; Indians of North America -- Florida -- History; Indians of North America -- Illinois Territory -- History; Mexican War, 1846-1848.; Philippine newspapers; Winnebago Indians; Albay (Philippines) -- History; Detroit (Mich.) -- History; Jefferson Barracks (Saint Louis, Mo.); Kentucky -- History -- Civil War, 1861-1865.; Massachusetts -- Description and travel; Michigan -- History -- War of 1812.; New Orleans (La.) -- Description and travel; New York (State) -- History -- War of 1812.; Newport Barracks (Ky.); Philippines -- History -- 1898-1946.; Philippines -- Politics and government -- 1898-1935.; Pennsylvania -- History -- Civil War, 1861-1865.; Regan Barracks (Philippines); Texas -- Description and travel; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; United States -- History -- War of 1812.